Efforts to Increase Self-Efficacy and Reduce Anxiety towards Learning Motivation through English Speaking Skills - Rindika Pramadanti Rindi (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2024)
This research aims to find out how self-efficacy influences students and reduces anxiety about speaking English so that it can increase learning motivation in students' speaking English skills at ASA Indonesia University. Speaking English is a challenge that is considered difficult due to a lack of self-efficacy and lack of motivation to learn, which causes anxiety in speaking English. Therefore, it is necessary to see what strategies lecturers use and how to increase self-efficacy in understanding motivation and reduce feelings of anxiety in speaking English. Several studies have examined learning motivation in improving English speaking skills. The respondents were 136 students at one of the leading private universities in Jakarta, Indonesia. The data collection method uses a questionnaire processed using SEM PLS version 3.2.9. This research found that several variables positively affected motivation to learn English, such as self-efficacy and anxiety in speaking English. Additionally, several variables can directly influence positive values ​​on English-speaking skills, such as self-efficacy and learning motivation, and negative values ​​on English-speaking skills, such as anxiety in speaking English. Apart from that, there is a direct positive influence on several variables that can influence English speaking skills through controlling learning motivation, including self-efficacy and anxiety in speaking English.